Peace Through Law The Versailles Peace Treaty and Dispute Settlement After World War I - Hess, Burkhard (Studies of the Max Planck Institute Luxembourg for International, European and Regulatory Procedural Law, 2019)
With the benefit of hindsight, presenting the Treaty of Versailles as an example of 'peace through law' might seem like a provocation. And yet, the extreme variety and innovativeness of international procedural and substantial 'experiments' attempted as a result of the Treaty of Versailles and the other Paris Peace Treaties of 1919-1920 remain striking even today. While many of these 'experiments' had a lasting impact on international law and dispute settlement after the Second World War, and considerably broadened the very idea of 'peace through law', they have often disappeared from collective memories. Relying on both legal and historical research, this book provides a global overview of how the Paris Peace Treaties impacted on dispute resolution in the interwar period, both substantially and procedurally. The book's accounts of several all-but-forgotten international tribunals and their case law include references to archival records and photographic illustrations.